2015
DOI: 10.1007/s13562-015-0314-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and proteomic analysis in two wild tomato lines under waterlogging and high temperature stress

Abstract: Tomato yields are reduced under waterlogging and high temperature stress condition. Ascorbic acid (ASA) was shown to be involved in tolerance to waterlogging and heat stresses in tomato. Among 44 wild tomato lines treated with waterlogging at 38°C, L6138 (Solanum peruvianum) showed highest ASA, shoot growth, chlorophyll content and chlorophyll fluorescence in comparison to other tomato lines. Further leaf proteins in L6138 and L0994 under waterlogging at 38°C for 72 h were analyzed by two-dimensional protein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 43 publications
(45 reference statements)
1
15
0
Order By: Relevance
“…The decrease in Fv/Fm was noted in more sensitive tomato and cucumber plants in our experiments. In agreement with our results, a decrease in Fv/Fm after waterlogging was also observed in rice [54,57], cucumber [56,58], tomato [59,60], wild tomato (Solanum habrochaites S.Knapp & D.M.Spooner) [61], Arabidopsis (Arabidopsis thaliana L.) [62], cotton [39], and pepper (Capsicum annuum L.) plants [63]. Barik et al [57] examined the reaction of tolerant and susceptible varieties of rice to submergence and observed that the latter exhibited a greater reduction in Fv/Fm parameters in comparison to tolerant varieties.…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in Fv/Fm was noted in more sensitive tomato and cucumber plants in our experiments. In agreement with our results, a decrease in Fv/Fm after waterlogging was also observed in rice [54,57], cucumber [56,58], tomato [59,60], wild tomato (Solanum habrochaites S.Knapp & D.M.Spooner) [61], Arabidopsis (Arabidopsis thaliana L.) [62], cotton [39], and pepper (Capsicum annuum L.) plants [63]. Barik et al [57] examined the reaction of tolerant and susceptible varieties of rice to submergence and observed that the latter exhibited a greater reduction in Fv/Fm parameters in comparison to tolerant varieties.…”
Section: Discussionsupporting
confidence: 92%
“…High-temperature stress represents one of the most frequent abiotic stresses worldwide, inducing several physiological and biochemical processes in cells, and limiting the growth and productivity of plants (Bita and Gerats, 2013 ). Plants respond to high temperature by reprogramming their proteome, metabolome and transcriptome to establish a new steady-state balance of metabolic processes (Kosová et al, 2011 ; Lin H. H. et al, 2015 ; Sruthi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high temperature combined with flooding can further compromise the performance of plant species through additional damages to the photosynthetic process, changes in root respiration, and also by compromising the synthesis of structural components (e.g., cell wall). However, it is important to note that only a few studies have addressed the links between these two stresses in great detail (Chen et al, , ; Donovan, Stumpff, & McLeod, ; Lin, Lin, Syu, Tang, & Lo, ), and thus, our knowledge about this topic, especially on wood species, is rather fragmented.…”
Section: Main Drivers Of Forest Dieback Under a Scenario Of Climate Cmentioning
confidence: 99%